Implementation of Maggot Cage Temperature and Humidity Control Using ESP8266 Based On the Internet of Things - Luluk Suryani; Ery Murniyasih; Marcelinus Petrus Saptono; Raditya Faisal Waliulu; Imam Trianggoro Saputro; Sony Rumalutur; Wennie Mandela (Ikatan Ahli Informatika Indonesia (IAII), 2022)
Black Soldier Fly (BSF) is a fly that can produce a maggot or larvae that are useful for human life, like a decomposer waste in the form of composting, animal feed, animal oil production, source of chitin, and for the economic incomes of the society. This study aims to develop a device that can be used to control the maggot cage temperature and humidity using the ESP8266 microcontroller based on the Internet of Things (IoT). The benefit of this study is the utilization of nozzle-based water spraying that can be used to maintain the maggot cage temperature and humidity to improve the quality of maggot cultivation results. In this study, the sensor used to read the temperature and humidity on the maggot cage is DHT11, then used a water spraying method to handle the temperature and humidity controlled by using the ESP8266 and online based on the Blynk IoT platform. This study result shows that the device built in this study can maintain the maggot cage temperature between 28 to 30oC and humidity over 60%.